Stand development stages and recruitment patterns influence fine-scale spatial genetic structure in two Patagonian Nothofagus species - Sola, Georgina Giselle; Marchelli, Paula; Gallo, Leonardo Ariel; Chauchard, Luis Mario; El Mujtar, Veronica Andrea (Springer, 2022)
Key message: Nothofagus alpina (Poepp. et Endl.) Oerst. and Nothofagus obliqua (Mirb.) Oerst forests have strong fine-scale spatial genetic structures. The intensity of genetic structure patterns differed according to species, stand development stages, life stages, and spatial arrangement of regeneration groups. This data becomes useful for forest management as it provides an understanding of how populations evolve as well as of the consequences of disturbances and enables the establishment of sampling strategies. Context: The understanding of fine-scale spatial genetic structure in natural populations is useful for forest management. Although Nothofagus alpina (Poepp. et Endl.) Oerst. and N. obliqua (Mirb.) are important species of the Patagonian forest, little is known about the genetic structure of their populations. Aims: The main objectives were to investigate the differences in fine-scale spatial genetic structure among mature tree populations of both species considering two stands at different development stages. Genetic structure was also evaluated among life stages and spatial distribution groups of regeneration within the old-growth stand. Methods: Genetic structure was examined by microsatellite DNA analysis of regeneration and mature tree populations of both species (around 1300 individuals). Gene dispersal distance was additionally estimated. Results: In both stands and species, strong fine-scale spatial genetic structure and short dispersal distance were found. This pattern was stronger in the early successional forest, in N. obliqua populations, in earlier life stages, and in scattered regeneration. Conclusion: Stand development stages and recruitment patterns influence the fine-scale spatial genetic structure of both Nothofagus species. However, the genetic structure also differs between species.